2011
DOI: 10.1063/1.3617458
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of Ag1−xGaTe2 with chalcopyrite structure

Abstract: In the present study, we investigated the high-temperature thermoelectric (TE) properties of AgGaTe2 with chalcopyrite structure. We tried to enhance the TE properties of AgGaTe2 by reducing the Ag content. The reduction of Ag increased the carrier concentration, leading to enhancement of the dimensionless figure of merit (ZT). The maximum ZT value was 0.77 at 850 K obtained in Ag0.95GaTe2, which was approximately two times higher than that of stoichiometric AgGaTe2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 27 publications
2
92
0
1
Order By: Relevance
“…The figure of merit, ZT, increased significantly from 0.53 for pure BiCuSeO to 0.9 for Bi 0.925 Ca 0.075 CuSeO at 923 K, which is higher than that of most thermoelectric materials with intrinsically low thermal conductivity reported thus far. [13][14][15][16][17][18][19][20] These results suggest that the BiCuSeO system is a robust candidate for medium-temperature thermoelectric applications. Further improvement in the ZT may be achieved by increasing the electrical conductivity via heavy hole doping either using conductive (Cu 2 Se 2 ) 2 À layers or insulating (Bi 2 O 2 ) 2 þ layers and/or by improving the carrier mobility.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The figure of merit, ZT, increased significantly from 0.53 for pure BiCuSeO to 0.9 for Bi 0.925 Ca 0.075 CuSeO at 923 K, which is higher than that of most thermoelectric materials with intrinsically low thermal conductivity reported thus far. [13][14][15][16][17][18][19][20] These results suggest that the BiCuSeO system is a robust candidate for medium-temperature thermoelectric applications. Further improvement in the ZT may be achieved by increasing the electrical conductivity via heavy hole doping either using conductive (Cu 2 Se 2 ) 2 À layers or insulating (Bi 2 O 2 ) 2 þ layers and/or by improving the carrier mobility.…”
Section: Discussionmentioning
confidence: 84%
“…22 The ZT value of Bi 0.925 Ca 0.075 CuSeO at 873 K is also higher than that of 0.7 for Bi 0.90 Sr 0.10 CuSeO at 873 K. 21 The present ZT of 0.9 is higher than most thermoelectric materials with intrinsically low thermal conductivity reported so far. [13][14][15][16][17][18][19][20] Therefore, it can be concluded that the higher thermoelectric performance of BiCuSeO is mainly due to the intrinsically low thermal conductivity of the material.…”
Section: Structural and Thermoelectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…580°C. [2,3] AgInTe 2 , on the other hand, reaches a ZT value of only 0.06 due to its low electrical conductivity, though the corresponding electrical bandgap of 1 eV is promising for the application as a solar cell material. [4] It crystallizes in the chalcopyrite structure type (space group I42d; CuFeS 2 -type) as derived from synchrotron powder diffraction data.…”
Section: Introductionmentioning
confidence: 97%
“…9 In order to further improve the TE performance, we need to explore new materials such as chalcopyrites CuGaTe 2 , 10,11 and AgGaTe 2 . 12,13 This kind of compounds were found to exhibit larger ZT value at high temperature region, which can be explained by significant decrease in the thermal conductivity at increased temperature.…”
mentioning
confidence: 94%